Quality Analysis For Defect And Defective Component Parts On Printed Circuit Board (Pcb) Using Dmaic Approach - Basir, Nor Afiza Abdul (Universiti Sains Malaysia, 2019)
In our daily lives, everything from our remote control devices to our vehicles includes electronic components. A printed circuit board (PCB) is made with fiberglass, copper lines and other metal parts, this board is held together with epoxy and insulated with a solder mask. Printed circuit board assembly (PCBA) process flow, the raw PCB will be registered by giving a serial number for each PCB at DOM Birthing which is placed at the front of each Bay before it is starting to be processed. To reach until final process which is Final Inspection (FNI) there will be many defects and defective occur. Defect product can be rework while defective product will be becoming scrap products which are no longer can be used. Thus, this problem will affect the production rate and customer demand. As a countermeasure, data collection is obtained to analyze data in more efficient methods and obtained the failure rates on the defects encountered in the production line. Data is being sorted and filter to narrow the research in order to find the most crucial root cause. DMAIC approach is used in order to analyze the data which is Define, Measure, Analyze, Improve and Control. Characteristic of the boards is studied in order to analyze the variety of product, PCB model, station, bay, defect, and defective type and also component. Data analysis allows one to answer questions, solve problems, and derive important information. Statistical and analytical tools are used to find the root cause and propose a solution to countermeasure the problems. Hence, it is necessary to find out the root cause of the rejection of the components or mechanical parts and also the remedy to reduce or if possible put a stop to the defects and defectives.